Application of Klampar Batik Branding as A Tactical Image Forming Factor (Case Study of Batik Center, Klampar Village) - A. B. Wibisono; A. T. Artanto; N. Anggriani (Future Science)
Branding in the SMEs (Small and Medium Size Enterprises) centers in the modern era is considered very necessary, so that economic progress and product stability in consumers are maintained dynamically. This research on Klampar Batik is an applied model of the results of previous research in the Batik center. The research with the theme